Effectiveness of Calcium Phosphate Desensitising Agents in Dental Hypersensitivity Over 24 Weeks of Clinical Evaluation - Usai, Paolo; Campanella, Vincenzo; Sotgiu, Giovanni; Spano, Giovanni; Pinna, Roberto; Eramo, Stefano; Saderi, Laura; Garcia-Godoy, Franklin; Derchi, Giacomo; Mastandrea, Giorgio; Milia, Egle (Nanomaterials (Basel, Switzerland), 2019)
Background: Calcium phosphate-based compounds are used to treat dental hypersensitivity (DH). Their long-term clinical behaviour needs further research. This study compared the 24-week effectiveness of Teethmate Desensitizer (TD), a pure tetracalcium phosphate (TTCP) and dicalcium phosphate dihydrate (DCPD) powder/water, to that of Dentin Desensitizer (DD), and Bite & White ExSense (BWE), both of calcium phosphate crystallites. Methods: A total of 105 subjects were selected. A random table was utilised to form three groups of 35 subjects. DH was evaluated using the evaporative sensitivity, tactile sensitivity tests, and the visual analogue scale (VAS) of pain. Response was recorded before the application of the materials (Pre-1), immediately after (Post-0), at 1 week (Post-1), 4 weeks (Post-2), 12 weeks (Post-3) and 24 weeks (Post-4). The non-parametric distribution was assessed with the Shapiro–Wilk statistical test. Intra-group differences for the six time points were evaluated with the Friedman statistical test and the Kruskal–Wallis test. Results: All the materials decreased DH after 24 weeks in comparison to Pre-1. However, the TTCP/DCPD cement showed the greatest statistical efficiency. Conclusions: The significant decrease of VAS scores produced by TD in the long term suggest the material as the most reliable in the clinical relief of DH.